Prevalensi Hepatitis B pada Komunitas Pria Homoseksual di Kota Bandung: Hepatitis B Prevalence in Homosexual Male Community in Bandung City - Naully, Patricia Gita (Universitas Muhammadiyah Sidoarjo, 2019)
Bandung is a city with the highest homosexual number in West Java. Homosexual is a term for someone having a sexual attraction to the same gender. The homosexual male community is more open to the public than the homosexual female. One of the health problems that is often suffered by the homosexual male community in various countries is Sexually Transmitted Infections (STIs) such as Hepatitis B. However, until now, the prevalence data of Hepatitis B in the community are very difficult to find in Indonesia. This study aimed to decide the prevalence of Hepatitis B in the homosexual male community in Bandung. The sample used in this study was 40 people. All samples were homosexual males fulfilling the inclusion criteria. The presence of Hepatitis B virus Surface Antigen (HBsAg) was detected by sandwich qualitative Enzyme-Linked Immunosorbent Assay (ELISA) method. Laboratory test results showed that 13 homosexual males were infected by the Hepatitis B virus. The majority of the sufferers have had risky sexual relations, such as changing partners, not using a condom, doing anal and oral sex. In addition, based on the interview results, it was known that all infected people have not received the hepatitis B vaccination when they are adult. Moreover, based on this study, it can be concluded that the prevalence of Hepatitis B in the homosexual male community in Bandung was 32.5%.